(untitled) (Papeles, 2021)
This paper reports a case study about a teaching and learning strategy in English Foreign Language (EFL) with 42 university students of the level A2. It was aimed to determine the effectiveness of a didactic sequence that integrated one element of digital technology (website) with one of analog technology (learning journal) within the Flipped Classroom Approach. The data were collected by using the learning journal, two focus groups, and a pretest and a posttest. The results showed that, although productive skills (speaking and writing) are the most difficult to develop in large groups of learners, these can be enhanced when there is a dynamic sequencing of the different class elements.